The Legality of a Party’s Call for Their Opponent’s Testimony in Civil Lawsuits - al-Mansour, Anees Mansour; Nasereddin, Tamara Yacoub (International Journal of Psychosocial Rehabilitation, 2020)
This study examines the legality of a party’s call to be made aware of their opponent’s testimony, whether their opponent be the plaintiff(s) or defendant(s). This study addresses the lack of a legal or juristic text that determines the legality of this matter and investigates the existence of contradicting and baseless legal judgements issued by the Court of Cassation. We found that it is illegal for a party to call for their opponent’s testimony as it may cancel out any primary means of evidence, such as a conclusive oath, judicial statement, or the outcome of a cross-examination. It may also allow adversaries to manipulate the legal organisation of a means of evidence by using it to avoid negative legal consequences that may occur. The study’s recommendations included having a straightforward text issued by the legislator specifying that opponents are not permitted to testify, and considering that text as part of the general system.